The Mediating Role of the Self-Concept Between the Relationship of the Body Satisfaction and the Intention to Be Physically Active in Primary School Students - Sánchez-Miguel, Pedro Antonio; León-Guereño, Patxi; Tapia-Serrano, Miguel Angel; Hortigüela-Alcalá, David; López-Gajardo, Miguel A.; Vaquero-Solís, Mikel (Frontiers in Public Health, 2020)
The aim was analysed the extent to which anthropometric values, in line with body image and physical ability, predict physical self-concept and the latter in turn predicts the practice and intention to pursue physical activity. A total 302 participants, 150 males and 152 females were recruited from different primary Schools in Extremadura (Spain). The age of the participants ranges of 10 – 13 years old (M = 11.74; SD = .86). The indirect effects of the model showed significant relationship between physical condition (p = .001) and PA levels, according to the perception of self-concept (β = .231, 95% BcCI = [.055, .212]). However, anthropometric variables proved not to be related to any significant extent (p <.05). The second level covered the indirect effects between the intention to be physically active and self-concept, which showed a significant relationship between the perception of self-concept (p = .000) and the intention to be physically active. Lastly, the third level showed significant relationships between physical condition (p = .001) and the intention to pursue physical activity. The present investigation concluded that physical condition, anthropometric variables and body image predict the perception of physical self-concept in adolescents.